Structural Equation Methods in the Social Sciences - Goldberger, Arthur S. (Econometrica, 1972)
[This survey of the use of structural equation models and methods by social scientists emphasizes the treatment of unobservable variables and attempts to redress economists' neglect of the work of Sewall Wright.]